Pengaruh Kualitas Pelayanan, Kepercayaan, Dan Harga Terhadap Kepuasan Pelanggan Raca Lele Di Tambun Utara - Fahsa, Nihanda Adnika; Suparman, Suparman (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study investigated the impact of service quality, trust, and price on customer satisfaction in the culinary enterprise Raca Lele, located in North Tambun. The research was prompted by recent fluctuations in customer volume and profitability observed by the business. A quantitative research design was adopted, employing a survey method with data collected through closed-ended questionnaires administered to 60 customers of Raca Lele. Data analysis was conducted using multiple linear regression, complemented by t-tests, F-tests, and coefficient of determination analysis, with the support of IBM SPSS version 26. The results revealed that, both individually and collectively, service quality, trust, and price exerted a positive and significant influence on customer satisfaction. These findings underscored the importance of enhancing service quality, building customer trust, and implementing competitive pricing strategies as critical components in fostering and maintaining customer satisfaction. The study offered practical implications for micro, small, and medium enterprises (MSMEs) seeking to develop effective strategies for improving service delivery and customer experience.